2020
DOI: 10.1016/j.patter.2020.100074
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning Approaches in COVID-19 Survival Analysis and Discharge-Time Likelihood Prediction Using Clinical Data

Abstract: Highlights d 1,182 hospitalized patients were studied in this research d Survival analysis can be applied to predict patient length of stay in the hospital d We used seven machine-learning and statistical analysis techniques d The impact of clinical covariates on survival times was studied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 31 publications
(28 reference statements)
6
75
0
2
Order By: Relevance
“…Logistic regression and separately LASSO regression were used to determine 10 variables that served as a significant predictor of a severe and critical COVID-19 infection. Nemati et al analyze survival characteristics of a group of 1,182 patients to test different variables of a patient and their overall survival to aid public health officials in their decisions regarding COVID-19 outbreaks (15). They discovered that gender and age were the two largest contributing factors to fatality, e.g., men had a higher fatality rate than women, agreeing with an original sample found in China early on (16).…”
Section: Related Workmentioning
confidence: 77%
“…Logistic regression and separately LASSO regression were used to determine 10 variables that served as a significant predictor of a severe and critical COVID-19 infection. Nemati et al analyze survival characteristics of a group of 1,182 patients to test different variables of a patient and their overall survival to aid public health officials in their decisions regarding COVID-19 outbreaks (15). They discovered that gender and age were the two largest contributing factors to fatality, e.g., men had a higher fatality rate than women, agreeing with an original sample found in China early on (16).…”
Section: Related Workmentioning
confidence: 77%
“…Few studies have also reported that being old or male, the probability of hospital discharge is lower. 22,23 Cox proportional hazards model has been used to study the mortality and recovery of COVID-19 patients. 10,11 The bias in estimating the hazard ratio of death in the presence of competing events have been investigated even in the context of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the early risk assessment for patients, in [114] demographic data, physiological clinical variables and laboratory results from electronic healthcare records are extracted and used with applied multivariate logistic regression, random forest and extreme gradient boosted trees. In order to predict survival analysis and discharge time based on clinical data, some machine learning algorithms are used in [115] . The data include various features including gender, symptoms, chronic disease history and travel history.…”
Section: Clinical Applicationsmentioning
confidence: 99%